Exploring Social Media Role in Zakat, Infaq, and Sedekah Administration - Assaidi, Sa'dullah; Nahar, Aida; ., Suhartono (International Journal of Zakat, 2024)
This study aims to explore the role of social media in driving zakat, infaq, and sedekah (ZIS) management. This study employs a qualitative method, operated upon the aspects of tasawur (general thought), epistemology, and analytical tools, as well as ushul al-fiqh, consisting of qawa’id (universal law), qiyas (analogical reasoning), dilalah (knowledge of meaning), tarjih (more valid law), and usuliyyah al-lughawiyyah (linguistic analysis) methods. Steps in this research include preliminary investigation, theoretical integration, empirical testing, documentation and human reflection on the process and outcome. The power of social media greatly influences the development of ZIS management in Indonesia. It can be a strength if used properly, transparently, and responsibly. Conversely, social media can become a boomerang when collecting ZIS irresponsibly, e.g., for personal gain.